(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
The utilization of discarded rubber tires contributes to environmental protection and helps in preserving natural aggregates. The proper disposal of waste materials is a significant global concern. The management of waste tires poses a major challenge since this material decomposes very slowly over time. For this universal concern, significant research inquiries have been conducted to explore diverse applications of rubber derived from tires crumb rubber. Across the globe are actively pursuing alternative substancesthatare economical and for the conservation of limited natural resources such as sand and aggregate. The focal point of this research involves the partial replacement of fine aggregate (by weight) with crumb rubber in M-25 and M-35 grade concrete mixes at various percentages: 0%, 5%, 10%, and 15%.